Judgment of the Court of Justice of the European Union of 30 April 2024 in the “EncroChat case” (case No. C-670/22): does this judgment really legitimise Forum Shopping in criminal proceedings, and how will it impact Lithuanian criminal proceedings? - Merkevičius, Remigijus (Teisė, 2024)
The article analyses the judgment of the Court of Justice of the European Union of 30 April 2024 in case No. C-670/22 (EncroChat) and its implications for Lithuanian criminal proceedings. According to this judgment, only a senior prosecutor can issue a European Investigation Order to obtain evidence already in the possession of the competent authorities of the executing state during a pre-trial investigation in Lithuania, and only the court hearing the criminal case can issue a European Investigation Order when the criminal case is in the hands of a court. The Code of Criminal Procedure of the Republic of Lithuania does not provide a legal basis for the prosecuting authorities to secretly intercept the content of all communications of the users of mobile telephones, which are fully encrypted by means of a special software and a modified device, and it is therefore questionable whether (i.) the transfer of the data obtained in this way to Lithuania as an extraditing state meets the substantive legal conditions arising from Article 162 of the CPC, which, according to the Code of Criminal Procedure of the Republic of Lithuania, defines the legitimacy of the use of the information obtained in another criminal proceeding, and whether (ii.) the data obtained by the receiving state by means of such a measure can be used in the criminal proceedings of Lithuania as an issuing state as evidence in an incriminating sense. If the executing State does not disclose the nature and essential technical characteristics of the means used to intercept the full content of the users’ communications by means of mobile telephones, which, by means of special software and a modified device, provide a fully encrypted connection, the defendants in general are deprived of an effective opportunity to know and present their position on these incriminating facts; therefore, such evidence is inadmissible in Lithuania’s criminal proceedings as an extraditing state.